PRINCIPAL'S ATTITUDE TO THE EXPANSION OF THE AUTONOMY OF THE INSTITUTION OF GENERAL SECONDARY EDUCATION: THE RESULTS OF ANALYTICAL RESEARCH - Kostiantyn Lynov; Iryna Lynova (Borys Grinchenko Kyiv Metropolitan University, 2021)
The authors of the article analyze the results of a survey of school principals conducted in December 2020 in Kyiv. The Law of Ukraine «On Education» provides for granting educational institutions the right to expand the scope of autonomy, namely - academic, organizational, personnel and financial autonomy. This process, among other things, depends on the level of readiness of the principals for self-government at school, the desire and ability to use the opportunities provided by the legislation of Ukraine. The purpose of the article is to publish the results of a study to determine the current state of the attitude of the head of the capital's school to the implementation of the declared autonomy of the school and the factors that prevent it. Realization of the set purpose provides the following: definition of the relation of the head of school to introduction of the autonomy of educational institutions declared by the legislation; determining the readiness of the head of the school in the near future to begin implementing the autonomy of the educational institution; identification of conditions, the satisfaction of which will be able to accelerate the introduction of autonomy of educational institutions. Participants in the survey «Autonomy of educational institutions and its impact on the quality of education management in the capital», conducted by the analytical center of Borys Grinchenko Kyiv University «OsvitAnalityka», were 472 principals of secondary schools and specialists of Kyiv education departments and the capital Department of Education and Science. This article presents an analytical review of the results of the survey of the heads of educational institutions in Kyiv, a statistical portrait of the school principals and the conclusions of the authors. Heads of schools in Kyiv support the ideas, possibilities of autonomy and introduce the autonomy of the educational institution with different speed, sequence of stages and a combination of components. The main conditions for the implementation of the autonomy of educational institutions, laid down by domestic legislation, leaders consider the following: development of an algorithm of actions for introduction of autonomy; training of school administration as educational managers; ensuring the appropriate level of current funding; deprivation of redundant functions of educational institutions; providing advisory assistance and developing a mechanism to encourage managers, etc.